2018
DOI: 10.1016/j.biortech.2018.01.060
|View full text |Cite
|
Sign up to set email alerts
|

Energy and greenhouse gas life cycle assessment and cost analysis of aerobic and anaerobic membrane bioreactor systems: Influence of scale, population density, climate, and methane recovery

Abstract: This study calculated the energy and greenhouse gas life cycle and cost profiles of transitional aerobic membrane bioreactors (AeMBR) and anaerobic membrane bioreactors (AnMBR). Membrane bioreactors (MBR) represent a promising technology for decentralized wastewater treatment and can produce recycled water to displace potable water. Energy recovery is possible with methane generated from AnMBRs. Scenarios for these technologies were investigated for different scale systems serving various population densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 30 publications
1
50
0
Order By: Relevance
“…(ii) lower energy consumption because no aeration is required. According to Pretel et al, (2014) in mild/warm climates AnMBR technology could be a net energy producer when treating low sulfate-loaded wastewater 6 ; (iii) lower greenhouse gas emissions, especially when methane is recovered from permeate 7 ; and (iv) potential resource recovery because biogas energy and nutrient enriched fertigation water are obtained from the anaerobic degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) lower energy consumption because no aeration is required. According to Pretel et al, (2014) in mild/warm climates AnMBR technology could be a net energy producer when treating low sulfate-loaded wastewater 6 ; (iii) lower greenhouse gas emissions, especially when methane is recovered from permeate 7 ; and (iv) potential resource recovery because biogas energy and nutrient enriched fertigation water are obtained from the anaerobic degradation process.…”
Section: Introductionmentioning
confidence: 99%
“…Mannina, Capodici, Capodici, Conseza, and Trapani (2018) further modeled GHG emissions in an IFAS process MBR and found a large variability depending on the carbon to nitrogen ratio. Cashman et al (2018) completed a life cycle assessment on GHG and energy, along with a cost analysis to provide various key performance characteristics needed when evaluating MBR technologies.…”
Section: Modelingmentioning
confidence: 99%
“…Cashman et al. (2018) completed a life cycle assessment on GHG and energy, along with a cost analysis to provide various key performance characteristics needed when evaluating MBR technologies.…”
Section: Modelingmentioning
confidence: 99%
“…The influence of treatment system capacity, degree of decentralization and treatment system technology has been evaluated using life cycle assessment (LCA) [23][24][25], LCA and life cycle cost assessment (LCCA) [26] and QMRA [10]. Both Cashman et al [26] and Kavvada et al [24,25] found that design flow or capacity economies of scale strongly influenced cost and environmental performance of decentralized membrane bioreactors (MBRs), with clear advantages for larger systems. However, they only evaluated larger, community-scale NPR systems, which have different distribution and collection requirements and pathogen risk profiles than single building systems.…”
Section: Introductionmentioning
confidence: 99%
“…AeMBRs are a common, commercially viable treatment option (Hai et al, 2019). AnMBRs were investigated to explore the energy recovery potential of onsite wastewater treatment (Cashman et al, 2018). RVFWs were selected as a lower-energy, natural treatment option that relies on active recirculation to achieve a smaller land requirement than traditional constructed wetlands (Arden and Ma, 2018;Gross et al, 2007).…”
Section: Introductionmentioning
confidence: 99%